Iraq : Second Review Under the Stand-By Arrangement, Requests for Waiver of Applicability, Extension of the Arrangement, and Rephasing of Access-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Iraq. (IMF Staff Country Reports; Country Report ;, 2011)
A financial program that aims to ensure macroeconomic stability of Iraq was discussed. The Iraqi economy was severely affected in 2009 by the decline in oil prices. Macroeconomic stability was maintained in 2010, despite a highly uncertain domestic and external environment. Policy discussions were framed by Iraq's medium-term prospects, especially with regard to the development of its vast hydrocarbon resources. Structural reforms under the program aim at improving public financial management.